2020
DOI: 10.3390/jcm9041093
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Profiles and Their Prognostic Relevance in Cardiac Amyloidosis

Abstract: This study sought to characterize cardiac amyloidosis (CA) patients with respect to hemodynamic parameters and asses their prognostic impact in different CA cohorts. Intracardiac and pulmonary arterial pressures (PAPs) are among the strongest predictors of outcomes in patients with heart failure (HF). Despite that, the hemodynamic profiles of patients with CA and their relation to prognosis have rarely been investigated. Invasive hemodynamic, clinical, and laboratory assessment, as well as cardiac magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Female predominance in HFpEF has been reported in former studies [ 8 , 20 ]. One explanation for this discrepancy with respect to PARAGON-HF may be that patients with a diagnosis of CA, which affects predominately male patients [ 21 ], were not explicitly excluded from PARAGON-HF, while every single patient in our registry underwent CA work-up before inclusion. In this context, the PARAGON-HF authors also assumed that amyloid cardiomyopathy may have accounted for the reduced responsiveness of sacubitril-valsartan in patients with higher EF [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Female predominance in HFpEF has been reported in former studies [ 8 , 20 ]. One explanation for this discrepancy with respect to PARAGON-HF may be that patients with a diagnosis of CA, which affects predominately male patients [ 21 ], were not explicitly excluded from PARAGON-HF, while every single patient in our registry underwent CA work-up before inclusion. In this context, the PARAGON-HF authors also assumed that amyloid cardiomyopathy may have accounted for the reduced responsiveness of sacubitril-valsartan in patients with higher EF [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“… 4 While pulmonary capillary wedge pressure and pulmonary artery pressure appear to be adverse prognostic markers in CA, the prevalence of PH and its haemodynamic profiles in CA are currently unknown. 5 6 …”
Section: Introductionmentioning
confidence: 99%
“…Three previous studies have reported on the frequency of increased biventricular filling pressure and compared potential difference between ATTR-CA and AL-CA. [4][5][6] While all 3 studies show that increase biventricular filling pressures were common, they showed disagreement when comparing AL-CA and ATTR-CA, with 1 study of 93 patients showing that AL-CA was associated with higher RAP and PCWP, 5 another study of 61 participants showed no difference in cardiac hemodynamics, 4 while a third study of 157 patients illustrated that ATTR-CA was associated with a higher systolic pulmonary artery pressure and PVR. 6 Our sample size (n=469) is larger than the aggregate of all previous studies (n=311).…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies have reported on the cardiac hemodynamic profiles in CA and the limited data show conflicting results as to whether ATTR-CA and AL-CA are affected by a same degree of hemodynamic alteration. [4][5][6][7] There is a need to understand the prognostic value of hemodynamic variables and pulmonary hypertension (PH) in CA.…”
mentioning
confidence: 99%